LESSONS FROM THE BHAGAVADGITA FOR MODERN MANAGEMENT PRACTICES - Rai, Shruti (ShodhKosh: Journal of Visual and Performing Arts, 2023)
India’s intellectual heritage has generated an extensive body of literature on fundamental issues like life, death, spirituality and the universe. When we look back at our legacy and understand it, we found that It’s not just knowledge, but continuing practice of wisdom, insight, and self-discovery. One such source of timeless knowledge is the Bhagavadgita. The Bhagavadgita, the most esteemed scripture of Hindu philosophy, has made significant contributions to the philosophical, religious, and spiritual domains of Hindu thought, earning great respect and acceptance among the global intellectual community—from scientists to spiritual figures. When we refer to Hindu thought, we are talking about the Hindu lifestyle, not the religion itself. Lord Krishna delivered this teaching on the battlefield of Kurukshetra to advise Arjuna about his responsibilities as a warrior to combat for justice. This ongoing counseling, spanning eighteen chapters, covers all management strategies aimed at attaining mental balance and overcoming crisis situations. Whether it is the transformation of human personality, achieved through a genuine comprehension of spirituality, into a vibrant, joyful existence that maintains equanimity in all situations, the ethical aspect of social existence, along with idea of Lokasangraha, focused training for optimal performance- all these crucial points of management have discussed in the Bhagavadgita. This is an effort to contemplate some lessons from the Bhagavad Gita and their relevance to contemporary management practices in the current global landscape, and how they might combine with Western approaches for an improved world.